ANALISIS FRAMING BERITA PENGUNGSI ROHINGYA PADA MEDIA ONLINE DI LIPUTAN6.COM DAN DETIK.COM TERHADAP OPINI PUBLIK - Laila, Putri Nur (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
ABSTRACT This study is entitled "Analysis of Rohingya Refugee News Framing on Online Media on Liputan6.com and Detik.com Against Public Opinion". This study uses William Gamson and Modigliani's framing analysis approach to analyze news about Rohingya refugees on Liputan6.com and Detik.com. The purpose of this study is to analyze how the framing of Rohingya refugee news is presented by the two online media, with a focus on the framing of Rohingya refugee news on Liputan6.com and Detik.com. The research method used is qualitative, with an in-depth analysis of news about Rohingya refugees on both media platforms. This study found that news on Liputan6.com and Detik.com tends to focus on the humanitarian aspect of the Rohingya refugee issue. The results of the study indicate that the framing applied by the two media influences public opinion with an emphasis on humanitarian issues. Keywords: Framing Analysis, News, Rohingya Refugees